2000
DOI: 10.1159/000010309
|View full text |Cite
|
Sign up to set email alerts
|

Pure versus Complicated Vulvar Vestibulitis: A Randomized Trial of Fluconazole Treatment

Abstract: Objective: To examine the effectiveness of a 6-month treatment consisting of a weekly oral dose of 150 mg fluconazole for women with vestibulitis, and to explore the causes of treatment failure. Methods: Forty women with vestibulitis were randomized to either of two treatment groups. One group received a 6-month low oxalate diet with calcium citrate complement, as a placebo, and the second group the same diet and calcium citrate with the addition of a weekly oral tablet of 150 mg fluconazole. The women were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 6 publications
1
24
0
1
Order By: Relevance
“…Although there have been case reports and uncontrolled studies (Meana & Binik, 1994), we have only been able to find only two randomized controlled trials which have been inspired by this approach. Both of these trials were directed at VVS patients and neither found that the medication investigated was better than placebo (Bornstein, Livnaat, Stolar, & Abramovici, 2000;Njirjesy et al, 2001). Recent sex therapy reviews have suggested that there are no empirically validated treatments for dyspareunia (e.g., Heiman & Meston, 1997).…”
Section: Are Therapies For Pain or For Sex More Effective In Treatingmentioning
confidence: 99%
“…Although there have been case reports and uncontrolled studies (Meana & Binik, 1994), we have only been able to find only two randomized controlled trials which have been inspired by this approach. Both of these trials were directed at VVS patients and neither found that the medication investigated was better than placebo (Bornstein, Livnaat, Stolar, & Abramovici, 2000;Njirjesy et al, 2001). Recent sex therapy reviews have suggested that there are no empirically validated treatments for dyspareunia (e.g., Heiman & Meston, 1997).…”
Section: Are Therapies For Pain or For Sex More Effective In Treatingmentioning
confidence: 99%
“…While Farage et al reported that up to 80% of women with vulvodynia have a self-reported history of recurrent vulvovaginal candidiasis, Bornstein noted that treatment with fluconazole did not improve vulvar pain symptoms among 40 women with vulvodynia, several of whom had culture-proven vulvovaginal candidiasis [17,18]. However, it is unclear whether symptoms were related to the topical therapies used for treatment or the candidal infection.…”
Section: Infectionmentioning
confidence: 99%
“…The heterogeneity of potential etiologies or the lack of a known etiology for VVS results in the use of multiple treatment regimens in clinical practice, including topical anti-inflammatories [42], corticosteroid injections [43], alpha interferon injections [44], tricyclic antidepressants [6,45], topical anesthetics [46], fluconazole [47], estrogen ointment [48], and surgical perineoplasty [49]. Most pharmacotherapies produce only minimal improvement in symptoms, which is similar to results seen in women receiving placebo in the few controlled trials that have been performed.…”
Section: Treatmentmentioning
confidence: 99%
“…On the basis of existing studies, the literature on the treatment of VVS can be divided into pharmacologic, behavioral, and surgical therapies. Within these categories only four randomized controlled trials exist [42,47,49,51] and only one was double-blinded [42] (Table 3). Bornstein et al [47] compared 6-month oral fluconazole therapy to low oxalate diet for treatment of VVS and found no significant difference in response rates between study groups.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation